Secretion of extracellular vesicles during ontogeny of the tapeworm Schistocephalus solidus - Mazanec, Hynek; Buskova, Nikol; Gardian, Zdenko; Kuchta, Roman (Folia parasitologica, 2023)
We provide the first ultrastructural evidence of the secretion of extracellular vesicles (EVs) across all parasitic stages of the tapeworm Schistocephalus solidus (Müller, 1776) (Cestoda: Diphyllobothriidea) using a laboratory life cycle model. We confirmed the presence of EV-like bodies in all stages examined, including the hexacanth, procercoids in the copepod, Macrocyclops albidus (Jurine, 1820), plerocercoids from the body cavity of the three-spined stickleback, Gasterosteus aculeatus Linnaeus, and adults cultivated in artificial medium. In addition, we provide description of novel tegumental structures potentially involved in EV biogenesis and the presence of unique elongated EVs similar to those previously described only in Fasciola hepatica Linnaeus, 1758 (Trematoda), Hymenolepis diminuta (Rudolphi, 1819) (Cestoda), and Trypanosoma brucei Plimmer et Bradford, 1899 (Kinetoplastida).
Keywords: ESP; cestodózy; Copepoda; Cestoda; zvířata; Extracellular Vesicles; novel tegumental structures; ultrastructure: EVs; Animals; Cestode Infections; Smegmamorpha; TEM; extracelulární vezikuly